2017
DOI: 10.1002/jsfa.8210
|View full text |Cite
|
Sign up to set email alerts
|

New propolis type from north‐east Brazil: chemical composition, antioxidant activity and botanical origin

Abstract: 'Jurema-preta' shoot apices are likely resin sources of RN propolis. The chemical characteristics and antioxidant property of RN propolis provide promising prospects for the introduction of this type of propolis into the apicultural market. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 36 publications
3
33
0
14
Order By: Relevance
“…Entretanto, trata-se de um tipo de própolis verde diferente daquela encontrada nas regiões sul e sudeste do país em sua composição química, evidenciado e sugerido por Ferreira et al (2017a) como uma resina originária de uma outra fonte botânica. Outro fato registrado foi a sua produção por duas espécies de abelhas distintas, Apis mellifera L. (africanizada) e Scaptotrigona postica (abelha sem ferrão) (FERREIRA et al, 2017a;FERREIRA et al 2017b, dados ainda não publicados).…”
Section: Fundamentação Teóricaunclassified
See 2 more Smart Citations
“…Entretanto, trata-se de um tipo de própolis verde diferente daquela encontrada nas regiões sul e sudeste do país em sua composição química, evidenciado e sugerido por Ferreira et al (2017a) como uma resina originária de uma outra fonte botânica. Outro fato registrado foi a sua produção por duas espécies de abelhas distintas, Apis mellifera L. (africanizada) e Scaptotrigona postica (abelha sem ferrão) (FERREIRA et al, 2017a;FERREIRA et al 2017b, dados ainda não publicados).…”
Section: Fundamentação Teóricaunclassified
“…Outro fato registrado foi a sua produção por duas espécies de abelhas distintas, Apis mellifera L. (africanizada) e Scaptotrigona postica (abelha sem ferrão) (FERREIRA et al, 2017a;FERREIRA et al 2017b, dados ainda não publicados).…”
Section: Fundamentação Teóricaunclassified
See 1 more Smart Citation
“…Although honey bees also behave as chewing insects when they collect plant resins, their mouth mandibles are delicate, as compared with mouth parts of typically chewing insects, such as leafcutter ants and grasshoppers. This is the probable reason why honey bees restrict the collection of plant resin to some exudates, e. g. from poplar apical buds, Clusia stigmata and stems of Dalbergia ecastophyllum [1], as well as tender plant parts, such as leaf primordia and apical buds of Baccharis dracunculifolia [4] and Mimosa tenuifolia [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, if we center our focus on Brazil, one of the top countries regarding propolis production and a country whose propolis is among the most studied in the world, it is surprising the low number of species which have been reported as propolis sources. In addition to the plants listed above (Baccharis, Clusia and Dalbergia), recently it has been shown that Mimosia tenuifolia (Leguminosae) from northeast Brazil is source of resin for a new type of green propolis [10]. Few other plant species have been suggested as sources of Brazilian propolis, among them Araucaria heterophylla [11] and Hyptis divaricata [12].…”
mentioning
confidence: 99%